Identity and built environment : issues for urban poor - Trivedi, Neeti (Curtin University, 2012)
The aim of the research was to examine redevelopment strategies and policies attempting to elevate the identity of the urban poor by reinforcing their socio-cultural characteristics through their built environment. The study also attempted to create a dialogue between identity and built environment and questioned whether a re-designed and re-developed environment can socially empower the urban poor; and, if so, what redevelopment strategies and approaches can be adopted to re-create identity and remove stigma over urban poor? Identity is the crest in the development of both people and place and cannot be viewed as an abstract or as a subject exterior to a human. But often, questions of ‘who we are’ (self-identity) are intimately related to questions of ‘where we are’ (place-identity) (Dixon and Durrheim 2000), creating a gap between structure and agency. This thesis not only analysed this gap but also measured the impact of poverty on the urban poor prevailing over their stigmatized identity linked to their built environment.It was important to understand an individual’s meaning of self, wherein ‘self’ is not just characterised and outlined by one’s association to the community, but also by an individual’s linkage to the diverse physical-setting that describe and construct their everyday life (Proshansky 1978, cited in Hillier 2002). It was also seen that individuals mostly describe ‘who’ and ‘what’ they are in the context of an intense sentimental connection to ‘house and home’ and/or ‘neighbourhood and community’. Thus, in relation to this research, an individual’s description of the physical world is limited to home and built environment.Additionally, this study explored strategies to overcome the multifaceted issues faced by the poor specifically linked to their built environment which contributes to their stigmatised identity (Davis 2006). Thereby, this thesis compared urban poverty in developed and developing countries within the built environment framework. The purpose was to identify the common aspects of built environment in both the contexts influencing the socio-cultural characteristics as well as well-being of the urban poor. The research thus searched for some common ground, where synergies were visible for future improvement works, globally.The process of examining built environment and measuring well-being of the urban poor, involved an analysis of Phillips and Pittman’s (2003) “Triarchic Model of Poverty” and Sen’s theory on “Capability and Well-being”(1993, cited in Fukuda-Parr 2003). This analysis helped define the evaluative factors for built environment and the indicators of well-being. The usage of this analytical framework was an iterative process which further assisted in auditing the redevelopment strategies of the urban poor applied during the case studies and in identifying those methodological and rational elements of the case studies that may be responsible for significant variations in the findings.In addition to theoretical literature reviews, four literature and two field case studies were conducted for the research. The literature case studies were focused on urban renewal examples providing an initial understanding of the concepts whereas the field case studies involving observations, discussions and surveys provided crucial insights to the intensity of the issue. Additionally, participation in the project provided valuable knowledge and better understanding of life in marginalised communities, their everyday practices, and of their socio-cultural and physical boundaries. Thus contact and dialogue with the stakeholders and reflection were the key tools performed during field trips to Victoria (Australia) and Ahmedabad (India).These field works were conducted with the main objective of studying the influence of redevelopment strategies on the well-being of urban poor. These redevelopment strategies were assessed using the analytical framework to identify the key built environment aspects having the maximum impact on identity renewal. Consequently, the three key aspects of built environment intervention identified were – housing and environment, pride and participation and government responsiveness.Through the assessment of the redevelopment strategies, it was deduced that development of housing and environment can bring a sense of stability and security, but ownership and belonging could be achieved only when there were signs of people’s participation and smooth efforts of the stakeholders for a holistic development. Similarly, it was recognised that urban renewal practices are not mere efforts towards renewing the built environment of the urban poor, but are also efforts to equip the people psychologically, socially, culturally and economically for the future in their own re-developed environment. Thus, within the framework of key built environment aspects, this thesis has proposed an identity renewal model promoting participatory approaches that collaborates with and incorporates not only citizens, but also organised interests, profit and non-profit organisations, planners and local administrators in a common frame. Such an integrated approach would ensure community interests, active citizenship and public-service delivery, where communication, learning, action and community welfare would co-evolve. Therefore, a model as projected for this research adopting joint planning and participatory approaches would help liberate the urban poor, permitting them to define and develop their own values and lead to their empowerment and identity creation.This thesis has thus proposed a positive course of action for future interventions to assist professionals and practitioners in conjunction with the barriers in the process in addition to a new model looking at identity issues of urban poor linked to their built environment.